Lip Schwannoma—A Rare Presentation in a Pediatric Patient: Case Report and a Literature Review - Cinzia Casu; Mara Pinna; Andrea Butera; Carolina Maiorani; Girolamo Campisi; Clara Gerosa; Antonella Caiazzo; Andrea Scribante; Germano Orrù (Diagnostics, 2025)
Background/Objectives: Schwannoma is a rare tumor, typical in young adults, originating from the myelin sheath that surrounds Schwann cells. It can occur in any part of the Peripheral Nervous System (PNS). It develops in the head and neck region in 25–48% of cases, and the eighth pair of cranial nerves (vestibulocochlear nerves) are the most hit (vestibular schwannoma). Oral cavity involvement is exceedingly rare, accounting for about 1–2% of all cases. The most affected oral site is the tongue, especially its anterior third, while localization on the lip is one of the least common sites for the development of this lesion. Case Presentation: A lower lip schwannoma on a 17-year-old boy, present for about 7 years, was documented. Material and Methods: PubMed and Google Scholar were used as research engines; English scientific works published in the last 20 years (2005–2024) regarding oral cavity involvement, using the keywords “Schwannoma”, “Oral Schwannoma”, “Pediatric Oral Schwannoma”, and “Schwannoma of the lip”, were considered. Results: In total, 805 and 16,890 items were found on PubMed and Google Scholar search engines, respectively. After title, abstract, full text evaluation, and elimination of duplicates, 26 articles were included in the review process. Discussion: Clinically, oral schwannoma presents as an asymptomatic hard–elastic fluctuating mass, often misdiagnosed on the lip as a traumatic or inflammatory lesion (e.g., mucocele). Biopsy is mandatory, and histological examination reveals positivity to the neuronal marker S-100. Conclusions: Complete excision also prevents recurrence. Malignant transformation is extremely rare.